Strategies for the prevention of chronic non-communicable diseases: a modern look at the problem - O. S. Kobyakova; E. S. Kulikov; R. D. Malykh; G. E. Chernogoryuk; I. A. Deev; E. A. Starovoytova; N. A. Kirillova; T. A. Zagromova; M. A. Balaganskaya (Кардиоваскулярная терапия и профилактика)
One of the most significant and urgent targets of modern healthcare is an effective control of chronic non-communicable diseases. These diseases lead not only to premature death, but also to permanent incapacitation and worsening of life quality. Prophylactic measures have proven to be the most effective method for control of chronic non-communicable diseases. However, in addition to well-known prevention tactics: population, high-risk and secondary prevention strategies, there are currently other approaches. The presented review provides a brief comparison of two “classical” prevention strategies. We analyzed the contribution of each of them to world healthcare, and justified the need for a complex approach to prevention. We studied possible transformation of present strategies and considered other promising approaches developed by some authors. Particular attention is paid to assessing the possibilities and feasibility of genetic information using to define the disease risks and personalize medical prevention.